Coenzyme Q10 in the Treatment of Corneal Edema in Kearns-Sayre: Is There an Application in Fuchs Endothelial Corneal Dystrophy?. Issue 9 (September 2016) - Kim, Jocelyn; Medsinge, Anagha; Chauhan, Bharesh; Wiest, Cara; Scanga, Hannah; Monaghan, Rachael; Moore, William H.; Nischal, Ken K.
Abstract : Purpose: Corneal involvement in mitochondrial disease is seldom described. Kearns-Sayre syndrome (KSS) is a mitochondrial disorder characterized by retinitis pigmentosa, external ophthalmoplegia, and heart block. We report 2 patients with KSS with corneal lesions involving the endothelium, which improved with Coenzyme Q10 (CoQ10). Based on recent research regarding the role of dysfunctional oxidative metabolism in Fuchs Endothelial Corneal Dystrophy (FECD), we propose that mitochondrial diseases and FECD share a final pathway. Methods: A chart review was performed and a review of the literature was completed with a PubMed search using the terms "Kearns-Sayre Syndrome", "mitochondria", "endothelium", "Fuchs endothelial corneal dystrophy", and "cornea". Results: There are 19 reports of corneal involvement in clinical phenotypes of mitochondrial disease. Nine of these 19 cases had findings consistent with KSS. Our patients with KSS had microcystic changes throughout the cornea and excrescences on the endothelial surface seen with ultrasound biomicroscopy, similar to the clinical findings in FECD. CoQ10 improved corneal disease in both children. CoQ10 deficiency has been reported in a variety of mitochondrial diseases, and efficacy of supplementation has been demonstrated. It may be beneficial in these patients because of its antioxidant properties and role in oxidative phosphorylation. Conclusions: The common deletion found in patients with KSS has recently been implicated in FECD, which has recently been shown to be a disease related to dysfunctional oxidative metabolism. Future research should explore the use of antioxidants, such as CoQ10 in patients with FECD. Abstract : Supplemental Digital Content is Available in the Text.